Impact of Medical Comorbidity and Risk of Death in 680 Patients with Alcohol Use Disorders. (15th January 2013) - Rivas, Inmaculada; Sanvisens, Arantza; Bolao, Ferran; Fuster, Daniel; Tor, Jordi; Pujol, Ramon; Torrens, Marta; Rey‐Joly, Celestino; Muga, Robert
Abstract : Background: The association between alcohol use disorders and increased risk of mortality is well known; however, there have been few systematic evaluations of alcohol‐related organ damage and its impact on survival in younger alcoholics. Therefore, we assessed medical comorbidity with a clinical index to identify subgroups of alcoholic patients at high risk of premature death. Methods: Hospital‐based cohort of alcohol‐dependent patients admitted for detoxification between 1999 and 2008 in Barcelona, Spain. At admission, sociodemographic characteristics and a history of alcohol dependence and abuse of illegal drugs were obtained through clinical interviews and questionnaires. Medical comorbidity was assessed with the Cumulative Illness Rating Scale (Substance Abuse) (CIRS‐SA). Dates and causes of death were obtained from clinical records and death registers. Survival was analyzed using Kaplan–Meier methods, and Cox regression models were used to analyze the risk factors for premature death. Results: Median age of the patients (686 total, 79.7% men) was 43.5 years (interquartile range [IQR], 37.8 to 50.4), average alcohol consumption was 200 g/d (IQR, 120 to 280 g/d), and duration of alcohol use disorder was 18 years (IQR, 11 to 24). Medical comorbidity by CIRS‐SA at admission showed that the organs/systems most affected were liver (99%), respiratory (86%), and cardiovascular (58%). After median follow‐up of 3.1 years (IQR, 1.5 to 5.1), 78 (11.4%) patients died with a mortality rate of 3.28 × 100 person‐years; according to Kaplan–Meier estimates, 50% (95% confidence interval [95% CI], 24 to 69%) of patients with severe medical comorbidity died in the first decade after treatment. In multivariate analysis, severe medical comorbidity (hazard ratio [HR], 5.5; 95% CI, 3.02 to 10.07) and being treated with methadone at admission (HR, 2.60; 95% CI, 1.50 to 4.51) were independent risk factors for premature death. Conclusions: Systematic assessment of alcohol‐related organ damage is relevant for the identification and treatment of those at increased risk of death.